“Ceramic Road” – Seen from Village Communal House Carving Art - Huong, Nguyen Thi Lan; Ngoc, Nguyen Hong (Journal of Ecohumanism, 2024)
Inheriting the essence of traditional art has always been considered the fulcrum for the development of modern art. Pottery Road is the sketch for viewers of artworks re-enacting important historical events of the country, and scenic spots along the quintessence of traditional pottery villages. The image of “Ceramic Road” in close relationship with regions in the country is also simulated by a 100m-long ceramic painting piece, using ceramic coated with a colored glaze, fired at a temperature of 1,200 degrees Celsius, ensuring durability stands firm against time. The ceramic path with the application of traditional artistic elements, although not a creative application, has also achieved certain successes.